PARITAS MEMPENGARUHI SIKAP IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN - Rahayu Dwikanthi; Jundra Darwanty; Retno Dumilah (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2020)
The inability of pregnant women conducting early detection of danger signs in pregnancy caused by less perceptions and attitudes of health. Many studies showed that the attitude of pregnant women have a correlation with the frequency of prenatal care visits, so it can make them have less exposed about information of their pregnancy. It can lead some complications and threatened the safety for both mother and fetus. One group pre-test and post-test research design was conducted in March to May 2019 in Karawang District.  The source of the data was questionnaires, performed on 67 pregnant women. Statistical analysis was performed with Chi square test and logistic regression. Bivariate analysis results showed that there were no significant differences between age, parity, and education with pregnant womenâ€™s attitude of danger signs in pregnancy in pre-test score. There were no significant differences between age and education with pregnant womenâ€™s attitude of danger signs in pregnancy in post-test score. Multivariable analysis results indicated that there was significant correlation between parity with pregnant womenâ€™s attitude of danger signs in pregnancy in post-test score. Conclusions: there are a correlation between parity with pregnant womenâ€™s attitude of danger signs in pregnancy. Health workers need to considering factors of parity when educated pregnant women about the danger signs in pregnancy.